Acute and late toxicities of patients infected with SARS-CoV-2 and treated for cancer with radiation therapy during the COVID-19 pandemic. (3rd October 2021) - Beddok, Arnaud; Chevrier, Marion; Calugaru, Valentin; Minsat, Mathieu; Dendale, Rémi; Lantz, Olivier; Servois, Vincent; Paoletti, Xavier; Crehange, Gilles
Abstract: Purpose: This study aimed to assess the risk of acute and late radiation-induced toxicity in patients with COVID-19. Material and methods: All the patients irradiated in Institut Curie from March to July 2020 were included if the first symptoms related to COVID-19 occurred no more than two months before the start of radiation therapy (RT) or 15 days after the end of RT. Results: Twenty-nine patients were included in this analysis. Twenty-five patients had no co-morbidities (86.2%), including morbid obesity. The diagnosis of COVID-19 infection was based on a positive SARS-CoV-2 RNA test for 18 patients (62.1%), a positive serology test for three patients (10.3%), and/or radiologic findings for 12 patients (41.4%). Three patients with symptoms highly suggestive of COVID-19 were included, although they had negative biologic tests and did not have a chest CT scan. Median time from the diagnosis of COVID-19 to the onset of RT was 5.5 days. Modification of RT course due to COVID-19 status was observed in 15 patients, including four for whom RT was definitively stopped. Six patients needed hospitalization for hypoxemic lung disease requiring intensive care. The majority of patients did not experience severe (> grade 2) acute toxicity. After a median follow-up of 6 months (IQR, 1–9 months), none of the patients had unusual clinical or radiological late toxicities. Conclusion: The observed acute and late toxicities were ultimately similar to those observed in a population not infected with COVID-19. These results do not prompt modification of standard RT protocols for irradiation of COVID-19 patients.